Enhancement of the Dissolution Rate of Ketoconazole Through a Novel Complexation with Humic Acid Extracted from Shilajit - P. AGARWAL, SURAJ; H. ANSARI, SHAHID; R. KARMARKAR, RITESH (Asian Journal of Chemistry, 2010)
The objective of the current research work was to investigate the potentiality of humic acid, extracted from shilajit, as a bioavailability enhancer. Ketoconazole was selected as a model drug because of its insolubility in water except at low pH, leading to poor bioavailability. Complexes of humic acid with ketoconazole were prepared in a molar ratio of 1:1 by solvent evaporation, spray drying and physical mixing methods. The prepared complexes were characterized by differential scanning calorimetry (DSC) and X-ray diffractometry (XRD). Phase solubility and intrinsic dissolution rate study of ketoconazole with humic acid were carried out in phosphate buffer of pH 5 and 6 to study the interaction between ketoconazole with humic acid. Phase solubility study indicates that solubility of ketoconazole was significantly increased at humic acid concentration greater than 0.8 % w/v due to micellization of humic acid. DSC and XRD studies showed differences between ketoconazole and ketoconazole-humic acid complexes prepared by various methods. Solvent evaporated and spray dried complexes showed significant improvement in dissolution rate as compared to ketoconazole or ketoconazole-humic acid physical mixture. Further, spray-dried complexes showed better dissolution rate than solvent evaporated complexes. The results indicate that the humic acid extracted from shilajit could be used to increase the dissolution rate and hence the bioavailability of poorly water-soluble drugs.